May Measurement Month 2018: an analysis of blood pressure screening from Kenya. (28th August 2020) - Ogola, Elijah N; Barasa, Anders; Gachemba, Yubrine M; Barasa, Felix; Gitura, Bernard M; Nalwa, Wafula; Wairagu, Anne; Beaney, Thomas; Ster, Anca Chis; Poulter, Neil R
Abstract: Hypertension (HTN) is highly prevalent and the leading cardiovascular risk factor for death globally. A large proportion of individuals with high blood pressure (BP) are unaware leading to under treatment and poor control. To address this, the International Society of Hypertension (ISH) initiated a global mass screening campaign, the May Measurement Month 2017 (MMM17), in which Kenya participated. Following the success of the campaign, its successor MMM18 was launched. Here, we present the Kenyan results for MMM18. Opportunistic screening of consenting adults was done in various sites across Kenya in May 2018, by volunteers trained using ISH material, under the co-ordination of the Kenya Cardiac Society. Blood pressure, pulse rate, weight, and height were measured by standard methods. Definitions of HTN and statistical methods all adhered to the standard MMM protocol. We screened 49 548 subjects, mean age 39.95 (15.3) years. In total, 49.4% had never had a BP measurement taken. After multiple imputation, 17.1% were hypertensive and of those who were hypertensive, 30.7% were aware, 26.6% were on antihypertensive treatment, and 13.0% had controlled BP. Alcohol use, excess weight, and treatment for HTN were associated with higher BP. The Kenyan MMM18 sites successfully screened more than three times the number screened in 2017, hence improving public awareness. Less than half the population had ever had a BP check. Less than a third of the hypertensives were aware with correspondingly poor treatment and control rates. Opportunistic mass screening is useful in raising public awareness.